De Novo Sequencing of Peptides from High‐Resolution Bottom‐Up Tandem Mass Spectra using Top‐Down Intended Methods. Issue 23 (20th December 2017) - Vyatkina, Kira; Dekker, Lennard J. M.; Wu, Si; VanDuijn, Martijn M.; Liu, Xiaowen; Tolić, Nikola; Luider, Theo M.; Paša‐Tolić, Ljiljana
Abstract: Despite high‐resolution mass spectrometers are becoming accessible for more and more laboratories, tandem (MS/MS) mass spectra are still often collected at a low resolution. And even if acquired at a high resolution, software tools used for their processing do not tend to benefit from that in full, and an ability to specify a relative mass tolerance in this case often remains the only feature the respective algorithms take advantage of. We argue that a more efficient way to analyze high‐resolution MS/MS spectra should be with methods more explicitly accounting for the precision level, and sustain this claim through demonstrating that a de novo sequencing framework originally developed for (high‐resolution) top‐down MS/MS data is perfectly suitable for processing high‐resolution bottom‐up datasets, even though a top‐down like deconvolution performed as the first step will leave in many spectra at most a few peaks.